Q. 103.6( 39 Votes )

# Find the relation

Answer :

Given: x = 3 and y = 1 is the solution of the given equations:

x – 4y + p = 0

and 2x + y – q – 2 = 0

To find: Relation between p and q

Proof:

On taking

-q – 2 = 2p

2p + q + 2 = 0

It is given that x = 3 and y = 1 is the solution of the equation

x – 4y + p = 0 …(i)

and 2x + y – q – 2 = 0 …(ii)

Substituting the value x = 3 and y = 1 in eq.(i), we get

(3) – 4(1) + p = 0

3 – 4 + p = 0

-1 + p = 0

p = 1

So, eq. (i) become

x – 4y + 1 = 0

Substituting the value x = 3 and y = 1 in eq.(ii), we get

2(3) + (1) – q – 2 = 0

6 + 1 – q – 2 = 0

-q + 5 = 0

q = 5

So, eq. (ii) become

2x + y – 5 – 2 = 0

or 2x + y – 7 = 0

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Glimpses of India39 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics